Rigging optimization for rowing efficiency - Kleshnev, V. (BioRow, 2022)
An interesting case occurred during our recent BioRow testing: a female single sculler (1.56m, 65kg) performed the standard BioRow step-test protocol (RBN 2013/04). Originally, the rigging was 0.88/2.85/1.60m (inboard/ oar length/ span), which made the static oar gearing ratio 2.077 very light even for this LW1x rowers` category (RBN 2020/07). Effect of light static oar gearing was multiplied by light dynamic gearing caused by short catch angles (about 53deg at low rates, down to 49deg at racing rate), which was related to long inboard and span at quite short athlete`s height. This made overall gearing too light, which was confirmed with "burden factors: both HDF (63-65 kg/m) and mass equivalent ME (37-39 kg over cycle) were much lower the average values for this category. The sculler had no problems with maintaining high racing stroke rate 35-36 spm, but struggled to "connect" with water and apply power: strokes looked too light and unproductive, speed target was not achieved.